DICA: destination intensity and congestion‐aware output selection strategy for network‐on‐chip systems. Issue 4 (15th April 2019) - Mehranzadeh, Amin; Khademzadeh, Ahmad; Bagherzadeh, Nader; Reshadi, Midia
Abstract : Selection strategy is an essential part of an adaptive routing algorithm that influences the performance of the networks‐on‐chip (NoC). A selection strategy is used for selecting the best output channel from the available channels according to the network status. This study presents a new output selection strategy called destination intensity and congestion aware (DICA) that uses both local and regional congestion information from adjacent and two hops away neighbours on the path to destination based on the channel and switch information. Also, the proposed output selection strategy uses a new global congestion‐aware scheme based on destination node called destination congestion awareness method to distribute traffic more equally over the network. The simulation results show that DICA strategy consistently improves the performance in both throughput and average latency with minimal overhead in terms of area consumption for various synthetic and real application traffic patterns. In addition, the microarchitecture of NoC routers is also presented in this study and it shows that the proposed output selection strategy can be combined with any adaptive routing algorithms. The experimental results show the average delay improvements of DICA to the Bufferlevel, neighbours‐on‐path, and regional congestion awareness are 87, 57, and 24%, respectively.